2015
DOI: 10.3324/haematol.2015.129510
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A mutations occur early or late in patients with myeloproliferative neoplasms and mutation order influences phenotype

Abstract: haematologica 2015; 100:e442 LETTERS TO THE EDITOR © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 15 publications
6
90
1
Order By: Relevance
“…JAK2 is the most frequently mutated gene in MPNs and JAK2-V617F (JAK2 V617F ) accounts for .95% of mutations of this gene (Kiladjian 2012). When co-occurring with DNMT3A mutations, the order of acquisition of DNMT3A and JAK2 mutations may be relevant in defining different MPN disease phenotypes (Nangalia et al 2015).…”
Section: Dnmt3a Mutations In Myeloproliferative Neoplasms and Myelodymentioning
confidence: 99%
“…JAK2 is the most frequently mutated gene in MPNs and JAK2-V617F (JAK2 V617F ) accounts for .95% of mutations of this gene (Kiladjian 2012). When co-occurring with DNMT3A mutations, the order of acquisition of DNMT3A and JAK2 mutations may be relevant in defining different MPN disease phenotypes (Nangalia et al 2015).…”
Section: Dnmt3a Mutations In Myeloproliferative Neoplasms and Myelodymentioning
confidence: 99%
“…63 As compared with TET2-first patients, JAK2-first patients were more likely to present with PV and to have a thrombotic event. More recently, the same group 64 has shown that DNMT3A mutations also may occur early or late in patients with an MPN, and that mutation order influences phenotype: overall, mutations BLOOD, 9 FEBRUARY 2017 x VOLUME 129, NUMBER 6 CLASSICAL MYELOPROLIFERATIVE NEOPLASMS 685…”
Section: Distinguishing Hereditary Disorders Attributable To Germ Linmentioning
confidence: 99%
“…Usually affecting a minority only of the myeloproliferative clone(s), they are thereby operationally defined as Bsubclonal^mutations for the purposes of this review. Most of these genetic abnormalities occur at the time of diagnosis, either preceding, accompanying, or following the appearance of phenotypic driver mutations [20,21,63], while some, such as mutations of JARID2 and TP53 [64,65], preferentially accumulate at the time of leukemic transformation. The same set of mutated genes occur in patients with myelodysplastic syndromes and acute leukemia; thereby, these mutations are not diagnostically relevant, if not because they point to the existence of a clonal myeloid disorder in patients in which no driver mutations are detected.…”
Section: Subclonal Mutationsmentioning
confidence: 99%
“…However, the mutational landscape of MPN in general, and of PMF in particular, appeared soon to be much more complex than initially though owing to the occurrence, particularly among patients with PMF, of additional mutations targeting genes involved in the epigenetic gene regulations, the spliceosome, or in oncogenes; these mutations are operatively called as Bsubclonal^since they usually occur in hematopoietic cell subclones of variable size, often but not invariably together with one of the phenotypic driver mutations, and may either antedate or follow the acquisition of phenotypic driver mutations [19]. The order by which these mutations appear in the mutational phylogenesis of MPN contributes to the disease phenotype, while the prognostic relevance if any is far from being appreciated [20,21]. Since these mutations are commonly represented also in myelodysplastic syndromes, other myeloid neoplasia, and acute leukemia, they have no specific diagnostic value, while, on the other hand, they contribute remarkably to the prognosis of patients with PMF.…”
Section: Introductionmentioning
confidence: 98%